ANALISIS PENGARUH HARGA, KUALITAS PELAYANAN, DAN KEBERAGAMAN PRODUK TERHADAP KEPUTUSAN PEMBELIAN MELALUI MINAT BELI SEBAGAI VARIABEL INTERVENING PADA TOKO FASHION MIA COLLECTION SITUBONDO - Mawardi, Farhan Khafi; Tulhusnah, Lusiana; Praja, Yudha (Fakultas Ekonomi dan Bisnis, 2024)
This study aimed to determine the role of buying interest in mediating price, service quality, and product diversity on purchasing decisions at Mia Collection Situbondo Fashion Store. The population in this study was consumers who bought products at the Mia Collection Situbondo Fashion Store. The sampling technique used in this study was probability sampling using a random sampling technique. Data analysis and hypothesis testing in this study used the Structural Equation Model—Partial Least Square (PLS-SEM). The results showed that price has a significant positive effect on purchase interest, service quality has a significant positive effect on purchase interest, product diversity has a significant positive effect on purchase interest, price has a significant positive effect on purchasing decisions, service quality has a positive but insignificant effect on purchasing decisions, product diversity has a positive but insignificant effect on purchasing decisions, purchase interest has a significant positive effect on purchasing decisions, price has a positive but insignificant effect on purchasing decisions through purchase interest, service quality has a positive but insignificant effect on purchasing decisions through purchase interest, and product diversity has a significant positive effect on purchasing decisions through purchase interest.